Granulocyte-colony stimulating factor may improve pregnancy outcome in patients with history of unexplained recurrent implantation failure: An RCT - Soheila Arefi; Elham Fazeli; Manijeh Esfahani; Nasim Borhani; Nazila Yamini; Ahmad Hosseini; Fattaneh Farifteh (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Family of colony-stimulating factors (CSF) have an essential role on early cross talk between embryo and uterine endometrium. Objective: The aim of this study was to evaluate the effects of the single dose of Granulocyte-CSF (G-CSF) injection on clinical outcome of assisted reproductive technology cycle in patients with repeated implantation failures. Materials and Methods: This randomized control trial study was performed on 52 infertile women who referred to the clinic with the history of more than three previous In vitro fertilization/Intracytoplasmic sperm injection-embryo transfer failures. All patients were stimulated with standard long protocol. All embryos were transferred on day five in blastocyst stage in both groups. The treated group received 300 μg (0.5 ml) recombinant human G-CSF subcutaneously which was injected 30 min before blastocyst embryo transfer. Results: There was not statistically significant differences in abortion rate in G-CSF and control group (p=0.09). G-CSF treated group showed higher clinical pregnancy rate in comparison with control group (56.2% vs. 40.0%) but it was not statistically significant (p=0.09). Although live birth rate in G-CSF group was higher than control group (53.1% vs. 35.0%) but there wasn’t statistically significant difference in the overall live birth rate between the two groups (p=0.10). G-CSF group had a twin pregnancies while in control group there was no twin pregnancy. Conclusion: Our result demonstrates the possibility that pregnancy outcome is better in women with repeated unexplained In vitro fertilization failure who are treated with G-CSF.